Expert consensus on the bone repair strategy for osteoporotic fractures in China - Zhang, Hao; Hu, Yan; Chen, Xiao; Wang, Sicheng; Cao, Liehu; Dong, Shiwu; Shi, Zhongmin; Chen, Yanxi; Xiong, Liming; Zhang, Yunfei; Zhang, Dianying; Yu, Baoqing; et al. (Frontiers in Endocrinology, 2022)
Osteoporotic fractures, also known as fragility fractures, are prevalent in the elderly and bring tremendous social burdens. Poor bone quality, weak repair capacity, instability, and high failure rate of internal fixation are main characteristics of osteoporotic fractures. Osteoporotic bone defects are common and need to be repaired by appropriate materials. Proximal humerus, distal radius, tibia plateau, calcaneus, and spine are common osteoporotic fractures with bone defect. Here, the consensus from the Osteoporosis Group of Chinese Orthopaedic Association concentrates on the epidemiology, characters, and management strategies of common osteoporotic fractures with bone defect to standardize clinical practice in bone repair of osteoporotic fractures.